Effects of Biochar Produced From Sugarcane Bagasse at Different Pyrolysis Temperatures on Water Retention of a Calcaric Dark Red Soil. Issue 1 (January 2016) - Kameyama, Koji; Miyamoto, Teruhito; Iwata, Yukiyoshi; Shiono, Takahiro
Abstract : Abstract: Biochar (BC) is a promising soil amendment that can enhance water retention and plant-available water capacity while mitigating CO2 emissions. We investigated the effect of sugarcane bagasse–derived BC on the water retention properties of a calcaric clay soil amended with 3% (wt/wt) BC produced at three pyrolysis temperatures (400°C, 600°C, and 800°C). For BC pyrolyzed at 800°C (BC800), water retention curves of soil amended at 1%, 5%, and 10% (wt/wt) were also measured. Water retention curves were measured immediately after amending soil with BC (all types and rates) and after a 180-day incubation period for soils amended with 3% BC. The hydrophobicity of BC pyrolyzed at 400°C (B400) was the highest of the three temperatures tested, resulting in the lowest water retained in soil amended with BC400, but only for measurements done before incubation. During incubation, the hydrophobicity of B400 decreased as the aliphatic compounds became exhausted by oxidation of the BC surfaces. The available water capacity of the clay soil increased significantly by more than 60% when amended with BC at rates greater than of 3% wt/wt ( P < 0.05).